ANALISIS NILAI-NILAI KARAKTER PADA BUKUKUMPULAN DONGENG SI KANCIL SEBAGAI ALTERNATIF BAHAN PEMBELAJARAN PKN KELAS I SEKOLAH DASAR - Luaiza Tamara, - (2021)
Humans are born to be good human beings and have character, character is the hallmark of a person that makes each individual different from other individuals. Cultivating character values can be done in the learning process in Civic Education (PKN) learning. In an effort to instill character values for elementary school students, learning materials are needed that contain interesting character values for students. The purpose of this study is to show learning materials in which there are character values in the book Fairy Tale of the Mouse Deer. The method used is the method of content analysis with analytical techniques (1) Adjusting the material into the subject of research data, (2) Analysis rules, namely the material is analyzed in stages following the procedure rules, by dividing the material into units, (3) Categories are the center From the analysis, aspects of interpretation follow the researcher's statement, are included in the category, (4) Criteria for credibility, and validation. Researchers found as many as 35 data findings in the story of the deer. Of the 35 data, there are 9 character values presented by the Ministry of National Education, the details are: (1) Religious 2. (2) Hard work 4. (3) Creative 7. (4) Curiosity is 7. (5) Appreciating achievement 2. (6) Friendly/communicative 4. (7) Peace-loving 2. (8) Social care 5. (9) Responsibility 2. Based on the results of the analysis, the dominant character values are creative character values and character values of curiosity know. Researchers make the results of the analysis to be used as an alternative learning material for PKN in Class I Elementary School. Keywords: Character, Learning Materials, PKN